SOSIALISASI PENINGKATAN PENGETAHUAN PENDERITA DIABETES MELLITUS TENTANG PEMERIKSAAN KADAR GULA DARAH DI DESA SEURIGET LANGSA BARAT KOTA LANGSA - Azwarni Azwarni; Elfida Elfida; Eva Sulistiany; Nora Hayani; Zulkarnaini Zulkarnaini (Bajang Institute, 2023)
Diabetes Mellitus is a non-communicable disease whose prevalence is increasing. A person is said to have diabetes if he has a fasting blood sugar level of >126 mg/dL and on a test when >200 mg/dL, Diabetes Mellitus is a cause of health problems in the world. There are many impacts caused by Diabetes Mellitus because the disease can affect all organs of the body and cause various kinds of complaints and complications so that sufferers will experience socio-economic changes and a decrease in quality of life. The purpose of the service is to increase the insight, knowledge and willingness of the community to independently check blood sugar levels. Participants in this activity were diabetes mellitus sufferers in Seuriget Village as many as 21 people. This community service method is by conducting counseling and demonstrations, checking blood sugar levels. This activity was carried out in May 2023. The result of the implementation of this activity was an increase in knowledge, namely before being given counseling the category was lacking, namely 81% after counseling 90.5% and the community's willingness to demonstrate self-checking of blood sugar levels to control blood sugar levels. To the public, especially people with diabetes mellitus, to be able to check blood sugar levels regularly and independently so that they can be controlled so as to reduce the impact of complications and improve quality of life